2017
DOI: 10.3389/fpls.2017.00262
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Identification, Classification, and Characterization of AP2/ERF Family Genes in the Desert Moss Syntrichia caninervis

Abstract: APETALA2/Ethylene Responsive Factor (AP2/ERF) is a large family of plant transcription factors which play important roles in the control of plant metabolism and development as well as responses to various biotic and abiotic stresses. The desert moss Syntrichia caninervis, due to its robust and comprehensive stress tolerance, is a promising organism for the identification of stress-related genes. Using S. caninervis transcriptome data, 80 AP2/ERF unigenes were identified by HMM modeling and BLASTP searching. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 71 publications
0
41
0
Order By: Relevance
“…AP2/ERF genes play central roles during plant stress responses and have been widely identified in both dicotyledonous and monocotyledonous plants using genomic or transcriptomic data [ 20 , 22 ], however, little is known about the functions of AP2/ERF genes in moss species. Several recent studies have demonstrated that AP2/ERF transcription factors play an important role in the stress responses of bryophytes [ 15 , 16 , 19 ]. B. argenteum is extremely tolerant to desiccation stress and is a promising model for the identification of stress related genes [ 8 ], however, no AP2/ERF gene in B. argenteum has been reported until now.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AP2/ERF genes play central roles during plant stress responses and have been widely identified in both dicotyledonous and monocotyledonous plants using genomic or transcriptomic data [ 20 , 22 ], however, little is known about the functions of AP2/ERF genes in moss species. Several recent studies have demonstrated that AP2/ERF transcription factors play an important role in the stress responses of bryophytes [ 15 , 16 , 19 ]. B. argenteum is extremely tolerant to desiccation stress and is a promising model for the identification of stress related genes [ 8 ], however, no AP2/ERF gene in B. argenteum has been reported until now.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AP2/ERFs also demonstrated to be the most abundant TFs in the DT moss Syntrichia caninervis [ 17 ]. The majority of DREB (Dehydration-Responsive Element-Binding Protein) genes in S. caninervis responded to dehydration and/or rehydration treatments [ 18 , 19 ], indicating that AP2/ERF transcriptional factors also play a central regulatory role during stress responses in moss species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been consensus that the conserved motifs of the AP2/ERF transcription factor are crucial to the function of transcription factors, such as nuclear localization and transcriptional activity [7]. The DNA binding domain of AP2/ERF transcription factors, i.e., AP2 domain, was highly conserved in plant species [50],[51]. The AP2 domain of the PgERF genes was also found to be highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…It has been the consensus that the conserved motifs of the AP2/ERF transcription factors are crucial to their functions, such as nuclear localization and transcriptional activity [7]. The DNA binding domain of AP2/ERF transcription factors, the AP2 domain, is highly conserved in plant species [50,51]. The AP2 domain of the PgERF genes is also highly conserved.…”
Section: Plos Onementioning
confidence: 99%